History of Nephrotic Syndrome and Evolution of its Treatment - Pal, Abhijeet; Kaskel, Frederick (Frontiers in Pediatrics, 2016)
The recognition, evaluation, and early treatment of nephrotic syndrome in infants and children originates from physicians dating back to Hippocrates. It took nearly another thousand years before the condition was described for its massive edema requiring treatment with herbs and other remedies. A rich history of observations and interpretations followed over the course of centuries until the recognition of the combination of clinical findings of foamy urine, swelling of the body, and measurements of urinary protein and blood analyses showed the phenotypic characteristics of the syndrome that were eventually linked to the early anatomic descriptions from first kidney autopsies and then renal biopsy analyses. Coincident with these findings were a series of treatment modalities involving the use of natural compounds to a host of immunosuppressive agents that are applied today. With the advent of molecular and precision medicine, the field is poised to make major advances in our understanding and effective treatment of nephrotic syndrome and prevent its long-term sequelae.